J5 Outcome in 25% at-risk individuals after presymptomatic testing for huntington's disease. (13th September 2016) - Bonnard, Adeline; Herson, Ariane; Staraci, Stephanie; Gargiulo, Marcela; Durr, Alexandra
Abstract : Background: Testing for Huntington's disease (HD) is usually restricted to individuals at 50% risk in whom the parent is diagnosed with HD. An individual at 25% risk requests testing with full knowledge that the transmiting parent does not want to know. International recommendations states that extreme care should be exercised when PT would provide information about another person who has not requested it. Aims: Since 1992, PT is offered in the Salpêtrière University Hospital in Paris. To i) compare outcome of 25% at risk individuals to those of 50%; ii) assess how test information was disclosed in the family and to the parent. Methods: We assessed information about pretest and post-test information including age, gender, parent status, motivation for testing, result of the PT and contacted 25% at risk individuals by phone and invited them for a semi-structured interview. Results: There were 1488 individuals at 50% risk and 159 at 25% who took the test between 1992 and 2016. Sixteen interviews in carriers and non carriers of the mutations were conducted, 5 lost to follow up. The mean time since testing request was similar in both groups [10.9 years ± 6.4 vs 11.4 years ± 6.5 p = 0.416]. 25% at risk were younger at first contact [30.7 ± 9.7 years (13–78) vs 35.1 ± 12.1 years (11–90), p < 0.001] and had less often children [42/153 (27%) vs 661/1437 (46 %), p = 0.001]. The 50% requested their result after multidisciplinary testing procedure more often than the 25% [1041/1488 (69.9%) vs 93/159 (58.5%), p = 0.001], and they were more often carriers of the mutation in HTT gene [42% (434/1041) vs 13% (12/93), p < 0.001]. Conclusions: Our results showed significant differences between the 25% and 50% at risk groups. In case of an unfavourable result, "double knowledge" had major implications for future relations between child and parent. Psychological issues, particularly the impact to become a "messenger of bad news" for parents and siblings were amplified in that case.